Broadband quarter-wave plate based on dielectric-embedded plasmonic metasurface - Owiti, Edgar O; Yang, Hanning; Ominde, Calvine F; Sun, Xiudong (Royal Society of Chemistry, 2017)
High transmission plasmonic and all-dielectric metasurface wave plates have been reported in recentstudies. However, narrow bandwidth and low polarization conversion need to be addressed to attaineven better operation requirements. In this work, we numerically demonstrate the concept of anultrathin single layer plasmonic metasurface embedded with dielectric resonators. Our design is based on the transmission line theory and surface plasmon excitation to realize a quarter-wave plate with controllable birefringence. The controllability is achieved through manipulating relative permittivity ofa non-dispersive dielectric material-embedded in a perforated silverfilm, and the surface dimensions of silver. We have also achieved higher degrees of linear-to-circular and circular-to-linear polarization conversions at broadband wavelengths in the near infrared compared with other conventional plasmonic metasurfaces. Moreover, the functioning of the wave plate is demonstrated on a compact and ultra thin metasurface showing great potential of integration into photonic sensors